Developing a Living Lab for Cross-Sectoral Collaboration in Sport, Physical Activity, and Health in the Rural Region Zeeland (Baltic Journal of Sport and Health Sciences, 2026)
Purpose: This project aims to strengthen local collaboration between stakeholders across the domains of sport, education, and health, to promote health-enhancing physical activity in the rural region of Zeeland. Rather than starting with predefined solutions, the initiative identifies key local challenges through collaboration within a Learning Network. These challenges include low participation in sport and physical activity, declining motor skills among youth, and limited integration of physical activity in healthcare. The innovative aspect of this initiative lies in its use of a Living Lab as a tool to foster real-life, co-creative problem-solving across sectors.Project: The establishment of the Learning Network for Sport, Physical Activity, and Health in Zeeland (SBGZ) emerged from the SPRONG PASS programme. This network brings together researchers, professionals, policymakers, citizens, students, and entrepreneurs to identify regional priorities and build collaborative structures. Based on insights from the Learning Network, multiple regional living labs were developed as a real-world environment for addressing shared challenges at the intersections of sport, health, and education. The Living Labs support cross-sectoral collaboration and facilitate joint problem-solving on locally relevant issues. Participatory action research is used to enable deep stakeholder engagement, empathy with target groups, and iterative co-creation of solutions. The effectiveness of collaborations and interventions is continuously evaluated and refined through participatory reflection and feedback loops. The approach is being scaled by establishing multiple local living labs and developing a transferable toolbox of methods, processes, and best practices. This is shared with other regions within SPRONG PASS Group and aligns with broader national policies on preventive health and wellbeing.Conclusion: This project demonstrates how a Living Lab approach can operationalise cross-sector collaboration in promoting physical activity and wellbeing. By focusing on local engagement and using participatory action research to bridge sectors, the project contributes to new methods for addressing complex societal challenges in an integrated, sustainable way.Keywords: Living Lab, learning network, cross-sector collaboration, participatory action research, community health